EXODUL DE CREIERI: CUM STIMULĂM TINERII SĂ RĂMÂNĂ/REVINĂ ÎN ŢARA DE ORIGINE? - USM ADMIN (Moldova State University, 2012)
This issue is actual and relevant not only for the Republic of Moldova. The brain drain circulation within academic mobility has both positive and negative effects and it is necessary to analyze the medium and long-term balance of these effects. In the Republic of Moldova the migration figures show a continuing growth. The negative impact of social, financial, institutional and political effects is more and more tangible. What could be the possible solutions for improving the flow of migration? The problem is very complex and involves many actors. In case of the Ministry of Education, the efforts must be focused on ensuring the appropriate, attractive and competitive educational framework. However, the national economic recovery would attract investments in the economic sector and create new jobs, providing good salaries for the young professionals. Fostering the employment of young people and promoting their career; the adjustment of the professional training to the market needs with an effective dialogue with economic actors; the use of migration processes aiming to develop the countries participating in the process - would reduce considerably the brain drain.